Network processes involved in the mediation of short-term habituation in Aplysia: contribution of intrinsic regulation of excitability and synaptic augmentation - Fischer, Thomas M.; Jacobson, Daniel A. (Frontiers in Integrative Neuroscience, 2014)
Short-term habituation (STH) is the decrease in behavioral responding observed during repeated stimulation at regular intervals. For siphon-elicited siphon withdrawal in Aplysia (S-SWR), we previously showed that the amplitude of responses measured in LFS-type siphon motor neurons (LFS MNs) during training is dependent on the stimulus interval used and is training-site specific. The major source of excitation from siphon stimulation onto the LFS MNs comes from the L29 interneurons. Here we examined the role of the L29s in STH by addressing two questions: 1. What are the relative contributions of intrinsic regulation of excitability and network inhibition on L29 activity during STH training? By activating L29s with intracellular current injection, we found that intrinsic changes in excitability occur, but only at short training intervals (1 sec). We also demonstrated that network inhibition is not required for regulating L29 responses during training, indicating that any expression of inhibition is redundant to the excitability changes. 2. How does L29 synaptic plasticity contribute to the maintenance of training site-specificity exhibited in LFS MNs? When training stimuli are delivered 1 sec apart (1 sec ISI), L29 responses decrease in both stimulated (trained) and un-stimulated (untrained) pathways, yet site-specificity of training is maintained in the LFS MNs. Our results suggest that activity-dependent synaptic facilitation (augmentation; AUG) expressed by the L29s acts to compensate for the decreased activity in the untrained pathway. First, we demonstrated that the L29-LFS synapse exhibits significant AUG with L29 activation at a 1 sec ISI. Second, we showed that the induction of AUG prevents the reduction in siphon-evoked LFS responses that is otherwise observed with decreased L29 activity. Collectively, our results support a role for the L29s in regulating network dynamics during STH training, but only at rapid (1 sec ISI) training intervals.